Physical and mechanical properties of local carbon materials and warm compaction method on the production of current collectors for light rail transit (LRT) applications / M. I. M. Ahmad ... [et al.] - Ahmad, M. I. M.; Muzafa, M. A. M.; Tahir, M. F. M.; Rahmat, M. S.; Sabri, M. A. M.; Selamat, M. (UiTM Press, 2024)
The purpose of this study is to investigate the physical and mechanical properties of local carbon materials and the warm compaction method in the production of current collectors for light rail transit (LRT) applications. The problem here is that the current collectors used by the railway industry in Malaysia for the LRT are still imported from foreign countries which is very costly. Furthermore, the production method of commercial current collectors, namely C-Cu composites, is compact and sintered, which also results in relatively high costs. Therefore, this study focuses on replacing the old materials and methods of commercial current collector production with new materials and methods. This study used a local carbon, which is the kernel shell of oil palm as the main carbon for the production of current collectors. The compact and sintered production methods are then replaced by warm compaction and post-heating methods.